Upper Hessenberg decomposition matrix utilized to build zero watermarking technique in YCbCr space - Mohammed, Nada Sabeeh; Abduldaim, Areej M. (AIP conference proceedings, 2022)
The properties of matrices as a subject in linear algebra are used in the topic of image processing via employing many algebraic methods in several areas, including security. The digital image watermarking techniques represent the security technique type addressed in this work. This paper aims to implement and demonstrate the possibility of successfully using the algebraic Hessemberge decomposition method (HDM) for the first time in building a zero watermarking technique as a transform to extract the features of the image without using any of the customary transformations. Also, the improvement of the results of the technique is performed by applying discrete wavelet transform (DWT) as an additional transform to increase the accuracy in the extraction of the watermark. Two techniques are adopted to achieve the aim. The basic idea behind both techniques is to make use of the algebraic Hessemberge decomposition method (HDM) as a mathematical tool to transform the image into another domain. In the first one, the YCbCr is applied to the color image to obtain the Y component. The HDM is carried out to create one matrix from the Hi matrices to get the master-secret. In the second technique, the DWT is utilized on the Y component to obtain the low-frequency band (LL). which is a low-resolution approximation of the original image. After that, the HDM is used to create one matrix from all the Hi matrices to get the master-secret. The experimental results show that the NC values under a lot of the attacks are improved in the second technique. But the NC values of salt and pepper attack in the first technique are higher. Some attacks retained the same values of the NC in both techniques.